Depressive symptoms in mothers of preterm infants before and during COVID-19 restrictions in neonatal intensive care units - Itoshima Ryo; Tuura Kirsi; Toome Liis; Varendi Heili; Saik Pille; Axelin Anna; Lehtonen Liisa; Ahlqvist-Björkroth Sari (WILEY, 2025)
Aim: Little is known about the specific restriction measures used in intensive care units (NICUs) during the COVID-19 pandemic and their impact on parental well-being. Hence, this study aimed to assess the association between restriction measures and mothers' post-partum depressive symptoms.
Methods: This comparative cohort study included mothers who gave birth before 35 weeks of gestation in Estonia. The outcome measure was mothers' post-partum depressive symptoms at the time of infant discharge, evaluated using the Edinburgh Postnatal Depression Scale (EPDS). In addition to the pandemic itself, the number of restriction measures in the NICUs was analysed as a potential explanatory factor for depressive symptoms.
Results:The study included 55 mothers before the pandemic in 2018-2019 and 54 mothers during the COVID-19 pandemic in 2021. No significant difference was found in the median EPDS scores between the cohorts: 7.0 [interquartile range (IQR): 4.0-12.0] and 8.0 (IQR: 5.0-12.8) respectively. The number of restriction measures was not associated with mothers' EPDS scores in either unadjusted or adjusted models.
Conclusion: The COVID-19 pandemic or the number of restriction measures used in Estonian NICUs did not associate with mothers' post = partum depressive symptoms.